The Role of the Vegfa C936t Polymorphism in the Development of Chronic Venous Insufficiency of the Legs And Its Analysis (Texas Journal of Medical Science, 2023)
In 98 patients, an analysis of the genetic risk factor for the development of chronic venous insufficiency was carried out by studying the frequency of distribution of alleles and genotypes of the C936T polymorphism in the VEGFA gene. In both groups, the actual distribution of C807T polymorphism genotypes corresponded to those expected under the Hardy-Weinberg equilibrium (p